Do (sex) crimes increase during the United States Formula 1 Grand Prix? - Piquero, Alex R. (Journal of experimental criminology, 2021)
Objectives We examine whether violent, property, or sex trafficking–related crime increased during the 2018 Formula 1 United States Grand Prix in Austin, Texas. Methods Ordinary least squares regression models, time series trend analysis, and forecasted prediction intervals based on autoregressive integrated moving average models are used to analyze daily crime incident data gathered by the Austin Police Department. Results There is no evidence to suggest a statistically significant increase in any of the analyzed crime types during the Formula 1 race weekend. Conclusions Our findings are directly relevant to the state of Texas’ human trafficking plan requirement for reimbursement from the state’s major events reimbursement fund. While we do not find the event increases crime, our data are limited to official crime incidents and exclude non-reported and undetected offenses. Future research should focus on potential differences between auto racing and other mega sporting events.